2011
DOI: 10.1121/1.3631561
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of the envelope of ultrasonic backscatter from human trabecular bone

Abstract: The paper describes the investigations intended to compare the results of experimental measurements of backscattering properties of the trabecular bone with the results of computer simulations. Ultrasonic RF echoes were collected using two bone scanners operating at 0.58 and 1.3 MHz. The simulations of the backscattered RF echoes were performed using the scattering model of the trabecular bone that consisted of cylindrical and spherical elements uniformly distributed in water-like medium. For each measured or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Backscatter data were gated to exclude the specular reflection at the front surface of the bone sample. Although backscatter measurements are less commonly used to characterize bone than attenuation and sound speed, many studies suggest that backscatter is a useful index of cancellous bone properties (Roberjot et al, 1996;Wear and Garra, 1998;Wear, 1999;Hoffmeister et al, 2000;Roux et al, 2001;Hoffmeister et al, 2002;Jenson et al, 2003;Wear and Laib, 2003;Hakulinen et al, 2005;Hakulinen et al, 2006;Jenson et al, 2006;Hoffmeister et al, 2006;Padilla et al, 2006;Riekkinen et al, 2007;Riekkinen et al, 2008;Ta et al, 2008;Padilla et al, 2008;Wear, 2008;Karjalainen et al, 2009;Litniewski et al, 2009;Litniewski et al, 2011;Hoffmeister, 2011;Padilla and Wear, 2011).…”
Section: Ultrasoundmentioning
confidence: 99%
“…Backscatter data were gated to exclude the specular reflection at the front surface of the bone sample. Although backscatter measurements are less commonly used to characterize bone than attenuation and sound speed, many studies suggest that backscatter is a useful index of cancellous bone properties (Roberjot et al, 1996;Wear and Garra, 1998;Wear, 1999;Hoffmeister et al, 2000;Roux et al, 2001;Hoffmeister et al, 2002;Jenson et al, 2003;Wear and Laib, 2003;Hakulinen et al, 2005;Hakulinen et al, 2006;Jenson et al, 2006;Hoffmeister et al, 2006;Padilla et al, 2006;Riekkinen et al, 2007;Riekkinen et al, 2008;Ta et al, 2008;Padilla et al, 2008;Wear, 2008;Karjalainen et al, 2009;Litniewski et al, 2009;Litniewski et al, 2011;Hoffmeister, 2011;Padilla and Wear, 2011).…”
Section: Ultrasoundmentioning
confidence: 99%
“…The acquired echoes, first corrected for TGC, were subsequently compensated for attenuation (Litniewski et al 2011). For each measured RF line, the following attenuation compensating algorithm was applied.…”
Section: Data Selection and Pre-processing For Statistical Analysismentioning
confidence: 99%
“…Using higher-frequency ultrasound was suggested to improve the correlation between entropy-based analyses and bone mineral density 25 . Moreover, it has been shown that the deviation of ultrasound backscattered statistics from Rayleigh distribution depends on the variation of trabeculae diameters and the number of thin trabeculae 33 . Other factors that are able to affect backscattered statistics include porosity, the directivity of trabeculae arrangement, variations in the trabeculae thickness, and periodicity or irregularity in the arrangement of scatterers 33 .…”
Section: Discussionmentioning
confidence: 99%